ANALISIS YURIDIS TERHADAP PEMALSUAN PAKAIAN MERK ‘RIP CURL’ DI UD RAHMAD KONVEKSI KOTA SAMARINDA BERDASARKAN UNDANG-UNDANG NO 15 TAHUN 2001 TENTANG MEREK - Arief Ramadhan (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
abstractIntellectual Property Rights ( IPR ) is closely related to the protection of the brand. But the problem is many businesses producing clothing under the brand of others without the original rights holder concerned . This is also reflected in the city of Samarinda ie businesses that produce clothing brand " Rip Curl " is not original .This study aimed to analyze the law enforcement against businesses that produce clothing brand " Rip Curl " are not original and what sanctions obtained by businesses that produce clothing brand " Rip Curl " that no original from the perspective of existing regulations and provide concepts against the government , businesses in order to create the rule of law in the production of clothing .Keywords : Intellectual Property Rights , Original and Not Original